Investigation on material variants and fabrication methods for microstrip textile antennas: A review based on conventional and novel concepts of weaving, knitting and embroidery. Issue 1 (31st December 2022) - Bulathsinghala, Rameesh Lakshan
Abstract: Wearable electronics sector is a fast-growing industry due to the rapid progress gained by developing textile-based conductive materials and conductive yarns. The demand for wireless communication in smart textiles has been increasing progressively, and therefore textile antennas will create potential benefits for wireless applications. Microstrip patch antennas play a major role in the field of textile antennas due to their low profile, conformal nature, compatible dimensions, and manufacturing feasibility. The performance of the microstrip patch antenna depends on the antenna dimensions, fabrication techniques and materials, which determine the antenna input impedance, gain, radiation efficiency, and bandwidth. The selection of correct materials, fabrication methods, and topology are very crucial for textile antennas. The heterogeneities in the textile material affect the quality factor and hence degrade the antenna performance. This article reviews conventional and novel fabrication techniques and material variants of each antenna component based on knitting, weaving, and embroidery in order to provide background information and application ideas for designing and developing microstrip patch antennas.